Return on Assets, Ukuran Perusahaan dan Debt to Equity Ratio Terhadap Earning Per Share - Riawan Awa Riawan (Trunojoyo University of Madura, 2020)
The purpose of this study is to see the effect of return on assets (ROA), company size, and debt to equity ratio to earnings per share (EPS). The analytical tool used in this study uses multiple regression analysis consisting of 3 (three) independent variables and 1 (one) dependent variable using the SPSS 20 application. Based on the results of the regression analysis and hypotheses performed, it shows that partially return on assets and measures the company has a positive and significant effect on earnings per share. While the debt to equity ratio has no significant effect on earnings per share.Keywords: return on assets, company size, debt to equity ratio, earnings per share